The Approximation Szász-Chlodowsky Type Operators Involving Gould-Hopper Type Polynomials - Behar Baxhaku; Artan Berisha (Abstract and Applied Analysis)
We introduce the Szász and Chlodowsky operators based on Gould-Hopper polynomials and study the statistical convergence of these operators in a weighted space of functions on a positive semiaxis. Further, a Voronovskaja type result is obtained for the operators containing Gould-Hopper polynomials. Finally, some graphical examples for the convergence of this type of operator are given.